Evaluation of asnaf entrepreneur’s strategic orientation on microenterprise performance - Hamdan, Hamdino; Zainol, Zaini (2015)
Most of the poor has high expectation for various forms of microfinancial sources from both the formal as well as the informal sectors. These sources of finance are highly needed by the poor to start and operate their productive activities such as microenterprises that generate sufficient income, hence relieve them from poverty. In addition, Islamic microfinance programme (IMP) which is based on Syariah and Islamic Finance concept has a very high potential in helping the poor to expand and diversify their economic activities, and increase their contribution towards the development of strategic entrepreneurial activities. IMP through the utilization of zakat fund has been a significant source of capital for entrepreneurship activities among the poor Muslim’s families in Malaysia. ‘Asnaf Entrepreneur Development Programme (AEDP)’ conducted by Lembaga Zakat Selangor (LZS) is among the pioneers and the most established IMP’s being introduced in Malaysia. Under the AEDP, part of the asnafs entrepreneur has exceeded the limits of poverty. Unfortunately, very few empirical studies have been conducted in Malaysia to identify the viability (resilience) of asnafs business involved with the IMP such as AEDP. Hence this study was conducted to evaluate the strategic orientation of the business operations run by asnafs entrepreneur. Results of the study show that business period, business classification, monitoring, fund size, purpose of loan usage and total income before participating in the microfinance programme, are the strategic factors which influence the level of income that asnaf entrepreneur can generate.